Characteristics and coinfection with syphilis in newly HIV‐infected patients at the University Hospital Dresden 1987–2012. (18th June 2014) - Spornraft‐Ragaller, Petra; Schmitt, Jochen; Stephan, Victoria; Boashie, Ute; Beissert, Stefan
Summary Background In Germany, notification data cannot be used to determine HIV and syphilis coinfection. No regional cohort has been studied for this in Eastern Germany. The rising incidence of syphilis from 2010 to 2012, predominantly in men having sex with men (MSM), has been suggested as a cause for recent increases in HIV infection rates in this group. Patients and methods Characteristics of 355 consecutive patients newly diagnosed with HIV infection at the University Hospital Dresden 1987–2012 were retrospectively compared to German surveillance data from the region of Dresden. Additionally, coinfection with syphilis was determined. Results Compared to German surveillance data, we observed higher proportions of persons originating from high prevalence countries and of AIDS cases. In the age group of up to 25 years, the proportion of MSM has risen 3‐fold since 2001. At time of HIV diagnosis, seroprevalence of syphilis was 20.3 %. Active syphilis (VDRL ≥ 1: 8) occurred in 6.7 % of patients, predominantly MSM, who also exhibited a significantly higher HIV viral load. Conclusions Our findings suggest a causative relationship between recently rising incidences of syphilis and HIV infection in MSM. Early diagnosis of syphilis may promote earlier diagnosis of HIV infection; therefore, HIV prevention measures should also include other sexually transmitted infections.